An analysis of the usefulness of readership research conducted by a midwestern daily newspaper - Gill, Karen L. (Kansas State University, 2024)
This case study attempted to determine whether a readership survey of a Midwestern daily newspaper was conducted and prepared according to accepted survey research standards for sampling the target population, dealing with nonresponse and writing survey questions. It also attempted to determine whether the readership survey results provided the newspaper's editors with the type of information they needed and wanted to know about reader and nonreader in order to make decisions about the newspaper's content. Information was gathered by conducting individual interviews with the survey's lead researcher and newspaper' executive editor and a focus group interview with the newspaper's other decision-making editors. Also the readership un e questionnaire and results report were compared to accepted survey research standards. The study 's findings were that the readership survey failed to meet survey research standards in each of the areas studied. The sampling methods used to recruit respondents could create bias for groups such as those at home more often and those with higher incomes. The survey questions were plagued with ambiguity, unintended meaning effects of social desirability and the use of various confusing rating scales. Because the newspaper executive editor reviewed the readership survey questions and had access to the results, the survey seemed to provide him with useful information. But the other editors were not involved in creating the survey or writing the questions. Their knowledge of the survey and its results was so limited as to render the survey practically useless to them.
Keywords: Newspapers; Midwest, United States; Readership Survey